Teaching Arabic Pegon through the AIR (Auditory Intellectually Repetition) Learning Model for New Female Students at the Tahfizh al-Qur'an Islamic Boarding School, Lirboyo - Siti Wahyuni; Tri Handriani (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to describe the implementation of the AIR (Auditory, Intellectually, Repetition) teaching model in Arab Pegon learning for new students of Class IV A1 at the Tahfizhil Qur’an Lirboyo Female Islamic Boarding School in Kediri, as well as to analyze the learning outcomes achieved. The AIR teaching model integrates three main stages: listening to explanations and asking questions for clarification (auditory), thinking critically and solving problems (intellectually), and repeating the material (repetition). This method was implemented to guide new students who require intensive assistance, both in mastering the technical aspects of reading and writing Arab Pegon and in building Islamic character.The results indicate that the application of the AIR teaching model significantly improves students’ ability to read Arab Pegon texts fluently, write accurately and neatly, comprehend text meanings, and translate them correctly into Indonesian. Learning success is influenced by factors such as students’ initial abilities, learning motivation, teaching methods and media, time availability, and facilities. Various supporting strategies were applied, including memorization, language comparison, translation, qosidah, and hands-on practice, tailored to the needs and learning styles of the students.These findings affirm that the AIR teaching model is effective in enhancing Arab Pegon literacy among new students in the pesantren environment, provided it is supported by varied teaching methods, effective time management, and a conducive learning environment.